Maternal satisfaction about the counseling in iron supplementation by health personnel - Dolores-Maldonado, Gandy (2018)
Introduction. The moment of counseling regarding supplementation is important, because it allows agreements for the benefit of the child’s health, which would later reach agreements that benefit the child's health. However, there is little information about maternal satisfaction during counseling. The objective of the present study was to determine the level of satisfaction of the mother regarding counseling provided by health personnel who provide the supplementation. Methods. A quantitative, descriptive and cross-sectional study was carried out with non-probabilistic sampling in Puente Piedra district, Lima - Peru, in 2016. 95 mothers with children under three years of age participated. Three dimensions of satisfaction (technical-scientific, interpersonal and comfort / communication support) were evaluated with a structured survey, validated by experts. The answers were rated between 0 and 3 points (yes: 3, regularly: 2, minimally: 1 and not: 0). The level of satisfaction was classified, adding the score of each answer, as: low, medium, high (0-7, 8-14, 15-21 points, respectively). The results are presented in frequencies and percentages (qualitative variables), and median and interquartile range (quantitative variables). Results The general satisfaction of the mothers was medium (45%), regarding its dimensions the technical-scientific was low (57%), and in the interpersonal and comfort / communication support dimensions it was medium (40% and 43%, respectively). Conclusion. There is a medium and low satisfaction in the counseling provided by health personnel who provide supplementation.